Introducing a new member of the genus Chlorophyllum: Chlorophyllum sapukai sp. nov., and new records from Paraguay - Maubet, Yanine (2022)
Discovered in Paraguay, Chlorophyllum sapukai is a new species based on morphological characters and multigene molecular phylogenetic analyses (ITS, LSU, RPB2 and TEF1 markers). Macroscopically, the species is characterized by large agaricoid basidiomata, with a hemispherical to broad convex pileus, a yellowish to cream buff surface of the pileus covered centrally with plate-like squamules. Microscopically, the new species is characterized by abundant cheilocystidia (35–50 × 14–20 µm), truncate basidiospores with a defined germ pore (9–10 × 6.5–7.5 μm), a pileus covering arranged as a trichodermial palisade at the squamules. Chlorophyllum hortense is recorded for the first time for Paraguay and the distribution of C. molybdites is expanded. Detailed morphological descriptions, field photographs of the species and the phylogenetic position of the Chlorophyllum species occurring in Paraguay are presented. A key to neotropical Chlorophyllum species is also provided.